14.6k views
1 vote
Find (f+g)(x) when f (x) =x^3-2x^3 +1 and g(x) =4x^3-5x+7

Find (f+g)(x) when f (x) =x^3-2x^3 +1 and g(x) =4x^3-5x+7-example-1
User Yosep Tito
by
4.7k points

1 Answer

3 votes

Answer:


{ \tt{(f + g)x = ( {x}^(3) - 2 {x}^(2) + 1) + (4 {x}^(3) - 5x + 7)}} \\ \\ { \tt{(f + g)x = ( {x}^(3) + 4 {x}^(3)) + ( - 2 {x}^(2) ) + ( - 5x) + (1 + 7) }} \\ \\ { \boxed{ \rm{(f + g)x = {5x}^(3) - 2 {x}^(2) - 5x + 8 }}}

User Matt Pavlovich
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.